Continuous Manufacturing of Pharmaceuticals 2017
DOI: 10.1002/9781119001348.ch5
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Crystallisation

Abstract: Mixing 2) Nucleation 3) Growth 4) Filter/wash/dry Required to:  Produce consistent composition  Control crystallisation driving force  Influence flow rate, shear-kinetic effects  Consistent suspension of seed and product Controlled via:  Supersaturation  High shear  External fields, e.g. ultrasound, nonphotochemical laser induced nucleation  Seed. Seeds produced via dry milling, wet media milling, precipitation, recycle, dissolution, spray drying or secondary nucleation Controlled to avoid:  Fouling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 164 publications
(145 reference statements)
0
6
0
Order By: Relevance
“…The most common type of continuous tank crystallizer is the mixed suspension mixed product removal (MSMPR) reactor system, , which could be operated in a single stage or in multiple stages. If the crystallization kinetics is fast, then plug flow crystallizers can be preferred ensuring efficient mixing and short residence time. ,, MSMPR, a key device in the continuous crystallization studies, is practically the same instrument that is utilized in batch processes. ,, In parallel, it performs the difficulties attached to batch equipment as well. Previous studies have reported simplicity, lower investment, and maintenance costs , as the main advantages of MSMPR crystallizers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common type of continuous tank crystallizer is the mixed suspension mixed product removal (MSMPR) reactor system, , which could be operated in a single stage or in multiple stages. If the crystallization kinetics is fast, then plug flow crystallizers can be preferred ensuring efficient mixing and short residence time. ,, MSMPR, a key device in the continuous crystallization studies, is practically the same instrument that is utilized in batch processes. ,, In parallel, it performs the difficulties attached to batch equipment as well. Previous studies have reported simplicity, lower investment, and maintenance costs , as the main advantages of MSMPR crystallizers.…”
Section: Introductionmentioning
confidence: 99%
“…If the crystallization kinetics is fast, then plug flow crystallizers 11 efficient mixing and short residence time. 7,12,13 MSMPR, a key device in the continuous crystallization studies, is practically the same instrument that is utilized in batch processes. 4,14,15 In parallel, it performs the difficulties attached to batch equipment as well.…”
Section: Introductionmentioning
confidence: 99%
“…Although continuous crystallization is already well established to manufacture large-volume commodity products such as sugar and inorganic salts, batch processing remains the method of choice in the pharmaceutical and fine chemical sector. In order to satisfy the high demands placed on the products resulting from these industry branches, continuous plant and equipment concepts are required that guarantee an enhanced control of the product quality attributes mentioned above. , …”
Section: Introductionmentioning
confidence: 99%
“…One possibility to realize a continuous process is the use of a cascade of multistage mixed suspension mixed product removal (MSMPR) crystallizers. These stirred vessels currently dominate in industrial crystallization processes and are preferably used when high residence times are needed, which may be the case if the desired crystalline product shows slow nucleation and low growth rates . Furthermore, this continuous crystallizer type is characterized by a highly efficient mixing, which has a positive effect on solid–liquid mass transfer, preventing fouling and blockage issues .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation